Mental Health as a Moderating Variable on The Influence of Self-Compassion and Work Environment on Subjective Well-Being - Thasya Namira; Survival; Nasharuddin Mas (Journal of Management Research and Studies, 2025)
This study aims to obtain empirical evidence of mental health as a moderating variable on the influence of self-compassion and work environment on subjective well-being. The study was conducted on employees of the Malang Middle Type Excise Supervision and Service Office (KPPBC TMC Malang). The population in this study were all employees totaling 102 people. The determination of the number of samples in this study used the Slovin formula, which was 81 respondents taken based on proportionate stratified random sampling. This study uses the SEM model with the Partial Least Square-Structural Equation Modeling (PLS-SEM) approach, and the statistical processing tool used is SmartPLS version 4. The results of the study indicate that higher self-compassion can increase subjective well-being. A better work environment can increase subjective well-being. Better mental health can increase subjective well-being. Mental health is able to act as a pseudo-moderation variable for the influence of self-compassion on subjective well-being. Mental health is unable to act as a predictor moderation variable for the influence of the work environment on subjective well-being.